Age-Related Inflammatory Balance Shift, Nasal Barrier Function, and Cerebro-Morphological Status in Healthy and Diseased Rodents - Varga-Medveczky, Zsófia; Kovács, Noémi; Tóth, Melinda E.; Sántha, Miklós; Horváth, Ildikó; Bors, Luca Anna; Fónagy, Katalin; Imre, Timea; Szabó, Pál; Máthé, Domokos; Erdő, Franciska (Frontiers in Neuroscience, 2021)
Increased blood–brain barrier (BBB) permeability and extensive neuronal changes have been described earlier in both healthy and pathological aging like apolipoprotein B-100 (APOB-100) and amyloid precursor protein (APP)–presenilin-1 (PSEN1) transgenic mouse models. APOB-100 hypertriglyceridemic model is a useful tool to study the link between cerebrovascular pathology and neurodegeneration, while APP–PSEN1 humanized mouse is a model of Alzheimer’s disease. The aim of the current study was to characterize the inflammatory changes in the brain with healthy aging and in neurodegeneration. Also, the cerebro-morphological and cognitive alterations have been investigated. The nose-to-brain delivery of a P-glycoprotein substrate model drug (quinidine) was monitored in the disease models and compared with the age-matched controls. Our results revealed an inflammatory balance shift in both the healthy aged and neurodegenerative models. In normal aging monocyte chemoattractant protein-1, stem cell factor and Rantes were highly upregulated indicating a stimulated leukocyte status. In APOB-100 mice, vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF-BB), and interleukin-17A (IL-17A) were induced (vascular reaction), while in APP–PSEN1 mice resistin, IL-17A and GM-CSF were mostly upregulated. The nasal drug absorption was similar in the brain and blood indicating the molecular bypass of the BBB. The learning and memory tests showed no difference in the cognitive performance of healthy aged and young animals. Based on these results, it can be concluded that various markers of chronic inflammation are present in healthy aged and diseased animals. In APOB-100 mice, a cerebro-ventricular dilation can also be observed. For development of proper anti-aging and neuroprotective compounds, further studies focusing on the above inflammatory targets are suggested.